PENGARUH DANA PIHAK KETIGA, TOTAL ASET DAN PEMBIAYAAN BAGI HASIL TERHADAP ROA UNIT USAHA SYARIAH BANK 9 JAMBI - Abdul Malik, Firdaus; Majid, Nazori; Fielnanda, Refky (Program Studi Manajemen Keuangan Syariah, 2023)
The purpose of this study was to determine the effect of TPF, Total Assets and Profit Sharing Financing on ROA at Bank 9 Jambi's Sharia Business Unit. The research method used is a quantitative method, with secondary data, in a multiple linear regression model. This study uses one dependent variable, namely the sharia business unit of bank 9 Jambi and independent variables, namely DPK, Total Assets and Profit Sharing Financing, with data collection techniques using the documentation method. Secondary data obtained from the website of Bank 9 Jambi. The results of the t-test in the study show that the DPK, Total Assets and Profit-sharing Financing variables have no effect on the Sharia Business Unit of Bank 9 Jambi. Based on the F-test, it was obtained that TPF, Total Assets and Profit Sharing Financing jointly affect the Sharia Business Unit of Bank 9 Jambi. Keywords: Third Party Funds, Total Assets, Profit Sharing Financing, Sharia Business Units.